The Impact of Aspect Ratio on External Heat Gain of Multi-storey Office Buildings in Jakarta - Iyati, Wasiska; Yulita, Eryani Nurma; Thojib, Jusuf; Sufianto, Heru (RUAS, 2018)
The narrow land in big cities such as Jakarta, increases the amount of high rise building, especially multi-storey office building. Office building consumes much energy to provide air conditioning to meet the thermal comfort inside the building. On the other hand, the building shape, building envelope, and building orientation to the sun's position are the main factors in building design aspects that affect the amount of cooling load. This study aims to investigate the impact of the aspect ratio or the ratio of the longer dimension of an oblong plan to the shorter, on external heat gain of multi-storey office building. Variables examined include the transparent and solid area of building envelope, the total area of the surface of the building envelope in any orientation, and the volume of the building, as well as the influence of those proportion on the external heat gain. This study uses mathematical calculations to predict the cooling load of the building, particularly external heat gain through the walls, roof and glass, as well as comparative analysis of models studied. The study also aims to generate the design criteria of building form and proportion of multi-storey office buildings envelope with lower external heat gain. In Jakarta climatic conditions, the result on rectangular building plan with aspect ratio of 1 to 4 shows that the external heat gain did not differ significantly, and the smallest heat gain is found on the aspect ratio of 1.8. Results also showed that the greater aspect ratio, the greater reduction of external heat gain obtained by changing the orientation of the longest side facing east-west into the north-south, about 2.79% up to 42.14% on the aspect ratio of 1.1 to 4. In addition, it is known that in same building volume, changing the number of floors from 10 to 50 can improve the external heat gain almost twice.